TEACHER‐CONDUCTED TRIAL‐BASED FUNCTIONAL ANALYSES AS THE BASIS FOR INTERVENTION1. Issue 1 (1st April 2013) - Bloom, Sarah E.; Lambert, Joseph M.; Dayton, Elizabeth; Samaha, Andrew L.
Abstract Previous studies have focused on whether a trial‐based functional analysis (FA) yields the same outcomes as more traditional FAs, and whether interventions based on trial‐based FAs can reduce socially maintained problem behavior. We included a full range of behavior functions and taught 3 teachers to conduct a trial‐based FA with 3 boys with developmental and intellectual disabilities who engaged in problem behavior. Based on the results of the trial‐based FAs, we developed and conducted 5 function‐based interventions, using differential reinforcement of an alternative behavior and extinction in all but 1 case. In the remaining case, we used noncontingent reinforcement. All interventions led to reductions in problem behavior and increases in alternative behavior.